INCREASE THE CAPACITY OF PHYSICIANS FROM RURAL REGIONS OF UZBEKISTAN BY EARLY DETERMINATION, EVALUATION AND TREATMENT OF CVDS( CARDIOVASCULAR DISEASE)AND DIABETES (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
The article focuses on enhancing the competency of physicians practicing in rural areas of Uzbekistan in the early detection, assessment, and management of cardiovascular diseases (CVDs) and diabetes. It delves into the significance of addressing these health issues promptly, especially in rural regions where access to specialized medical care might be limited. The article highlights the importance of equipping rural physicians with the necessary knowledge, skills, and resources to identify risk factors, conduct screenings, and initiate appropriate interventions for patients at risk of or affected by CVDs and diabetes. By empowering rural physicians in this manner, the article aims to improve healthcare outcomes, reduce disease burden, and enhance overall public health in Uzbekistan's rural communities.